KAJIAN KARAKTERISTIK DANAU PASCATAMBANG PROBO, DESA TAMAN SARI, KECAMATAN RUMPIN, KABUPATEN BOGOR, JAWA BARAT - Irene Kreuta; Edy Jamal Tuheteru; Suliestyah (Jurnal Riset Multidisiplin Edukasi, 2026)
Post-mining lakes are formed as a result of mining activities and continue to undergo physical and environmental changes after mine closure. Understanding their morphological development and water quality is essential to support sustainable environmental management. This study aims to examine the characteristics of the PT X post-mining lake in Taman Sari Village, Rumpin District, Bogor Regency, through morphological change analysis and water quality assessment. The research was conducted using field surveys, historical imagery analysis, three-dimensional (3D) modeling, and water quality testing. The results show that the lake has experienced significant morphological changes, particularly due to the expansion of vegetation cover across most of its surface. Overall, the water quality meets the Class IV standards stipulated in Government Regulation of the Republic of Indonesia No. 22 of 2021 (Appendix VI), although low dissolved oxygen (DO) and relatively high iron (Fe) concentrations indicate the need for continuous monitoring and sustainable management.